Przemysł okrętowy rozszerzonej Unii Europejskiej w procesie globalizacji gospodarki światowej - Jeliński, Bohdan (The Shipbuilding Industry of the Enlarged European Union, 2005)
The shipbuilding industry is a socially, economically, politically and militarily important part of the European Union economy. In the world shipping market, which for a long time now has been global in nature, European shipyards play an important, though diminishing role. Aiming at maintaining its shipbuilding industry in a manner guaranteeing its international sustainability the EU has developed the LeaderSHIP 2015 plan. It is an active and creative reply to the challenge posed by the process of globalization of the world's economy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1066, s. 132-142